Analisis Bauran Pemasaran Produk UMKM (Studi Kasus: Produk UMKM Ekowisata Harangan Girsang, Kabupaten Simalungun, Sumatera Utara) - Deafani Clara Sinaga; Sumihar Sebastiana Sitompul; Riana Handayani Silalahi; Sepdwiyana Donargo; Toni Jeremia Purba (Yayasan Literasi Sains Indonesia, 2025)
This study aims to provide a comprehensive overview of marketing practices by Harangan Girsang Ecotourism MSMEs using the 7P marketing mix: Product, Price, Place, Promotion, People, Process, and Physical Evidence. This research is descriptive qualitative. Research data were collected using observation, literature studies, and interviews with the head of the Harangan Nauli Pokdarwis, the head of the Forest Farmer Group (KTH), and MSMEs of the Tourism Village. The results, Product: MSMEs in Harangan Girsang Village have displayed the characteristics of culinary processed MSME products such as kecombrang syrup, Hassang Girsang, and itak gurgur, but still need product innovation. Price: The pricing strategy for MSME products is affordable, but have not been able to align competitive prices with decent profit margins. Place: distribution of MSME products in Harangan Girsang Paradise Ecotourism is using direct sales. Promotion: the use of social media such as Instagram and TikTok has begun but is still not consistent in the schedule of uploading content and the preparation of content that still monotonous. People: Currently there needs to be synergy between the younger generation of the village so that they can appear as a driving force for innovation in the development and marketing of MSME products. Process: Sales and distribution of MSME products are carried out directly at MSME stalls in Harangan Girsang Ecotourism, but there is no SOP implemented yet. Lastly, Physical Evidence: there are already stalls available at the Harangan Girsang Paradise Ecotourism, the layout is quite neat, and the cleanliness is well maintained.